Internalisasi Nilai Nilai Pendidikan Islam dalam Lagu “Membasuh” Karya Hindia: Analisis Hermeneutika Lirik dan Kontekstualisasi Pendidikan Akhlak - Ramadhani, Dwi; Erdanu, Albrillyant Rizky (JOIES (Journal of Islamic Education Studies), 2025)
This study aims to analyze the internalization of Islamic educational values in the song “Membasuh” by Hindia through a hermeneutic approach. The song was chosen because it contains moral and spiritual messages that align with Islamic teachings, although expressed through a popular cultural medium. This research employs a qualitative descriptive method with hermeneutic analysis to interpret the implicit meanings behind the song’s lyrics. The primary data consist of the “Membasuh” lyrics, while secondary data are drawn from Islamic education literature, hermeneutic theory, and relevant Qur’anic verses and hadiths. The findings reveal that “Membasuh” embodies eight core values of Islamic education: sincerity (ikhlas), patience (sabr), asceticism (zuhd), cooperation (ta’awun), compassion (rahmah), forgiveness (‘afw), excellence (ihsan), and steadfastness (istiqamah). These values reflect the human spiritual journey toward moral awareness and servitude to Allah. The song also holds pedagogical relevance, as it can serve as a reflective medium in teaching Islamic ethics, particularly for younger generations who are familiar with digital media and popular music. In conclusion, Hindia’s work demonstrates that Islamic educational values can be contextually and humanistically internalized through artistic and cultural expression.